Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's analyze each equation step-by-step to determine which ones are quadratic functions.
### Step-by-Step Solution:
1. Equation 1: [tex]\(2b(b-7) + b = 0\)[/tex]
- Start by expanding and simplifying the expression on the left-hand side:
[tex]\[ 2b(b - 7) + b = 2b^2 - 14b + b = 2b^2 - 13b \][/tex]
- This can be written as:
[tex]\[ 2b^2 - 13b = 0 \][/tex]
- Since the highest power of [tex]\( b \)[/tex] is 2, this is a quadratic equation.
2. Equation 2: [tex]\((4a + 2)(2a - 1) + 1 = 0\)[/tex]
- Begin by expanding the expression:
[tex]\[ (4a + 2)(2a - 1) + 1 = 8a^2 - 4a + 4a - 2 + 1 = 8a^2 - 1 \][/tex]
- This simplifies to:
[tex]\[ 8a^2 - 1 = 0 \][/tex]
- Since the highest power of [tex]\( a \)[/tex] is 2, this is a quadratic equation.
3. Equation 3: [tex]\(2y + 2(3y - 5) = 0\)[/tex]
- Expand and simplify the expression:
[tex]\[ 2y + 2(3y - 5) = 2y + 6y - 10 = 8y - 10 \][/tex]
- This results in:
[tex]\[ 8y - 10 = 0 \][/tex]
- The highest power of [tex]\( y \)[/tex] is 1, so this is a linear equation, not a quadratic equation.
4. Equation 4: [tex]\(8 - 5x = 4(3x - 1)\)[/tex]
- Expand and simplify the expression:
[tex]\[ 8 - 5x = 12x - 4 \][/tex]
- Combine like terms:
[tex]\[ 8 + 4 = 12x + 5x \implies 12 = 17x \][/tex]
- The highest power of [tex]\( x \)[/tex] is 1, so this is also a linear equation, not a quadratic equation.
### Conclusion:
The quadratic equations among the given options are:
- [tex]\(2b(b-7) + b = 0\)[/tex]
- [tex]\((4a + 2)(2a - 1) + 1 = 0\)[/tex]
So, the quadratic functions are:
1. Equation 1: [tex]\(2b^2 - 13b = 0\)[/tex]
2. Equation 2: [tex]\(8a^2 - 1 = 0\)[/tex]
Thus, the quadratic functions are the ones represented by [tex]\( \text{eq1} \)[/tex] and [tex]\( \text{eq2} \)[/tex].
### Step-by-Step Solution:
1. Equation 1: [tex]\(2b(b-7) + b = 0\)[/tex]
- Start by expanding and simplifying the expression on the left-hand side:
[tex]\[ 2b(b - 7) + b = 2b^2 - 14b + b = 2b^2 - 13b \][/tex]
- This can be written as:
[tex]\[ 2b^2 - 13b = 0 \][/tex]
- Since the highest power of [tex]\( b \)[/tex] is 2, this is a quadratic equation.
2. Equation 2: [tex]\((4a + 2)(2a - 1) + 1 = 0\)[/tex]
- Begin by expanding the expression:
[tex]\[ (4a + 2)(2a - 1) + 1 = 8a^2 - 4a + 4a - 2 + 1 = 8a^2 - 1 \][/tex]
- This simplifies to:
[tex]\[ 8a^2 - 1 = 0 \][/tex]
- Since the highest power of [tex]\( a \)[/tex] is 2, this is a quadratic equation.
3. Equation 3: [tex]\(2y + 2(3y - 5) = 0\)[/tex]
- Expand and simplify the expression:
[tex]\[ 2y + 2(3y - 5) = 2y + 6y - 10 = 8y - 10 \][/tex]
- This results in:
[tex]\[ 8y - 10 = 0 \][/tex]
- The highest power of [tex]\( y \)[/tex] is 1, so this is a linear equation, not a quadratic equation.
4. Equation 4: [tex]\(8 - 5x = 4(3x - 1)\)[/tex]
- Expand and simplify the expression:
[tex]\[ 8 - 5x = 12x - 4 \][/tex]
- Combine like terms:
[tex]\[ 8 + 4 = 12x + 5x \implies 12 = 17x \][/tex]
- The highest power of [tex]\( x \)[/tex] is 1, so this is also a linear equation, not a quadratic equation.
### Conclusion:
The quadratic equations among the given options are:
- [tex]\(2b(b-7) + b = 0\)[/tex]
- [tex]\((4a + 2)(2a - 1) + 1 = 0\)[/tex]
So, the quadratic functions are:
1. Equation 1: [tex]\(2b^2 - 13b = 0\)[/tex]
2. Equation 2: [tex]\(8a^2 - 1 = 0\)[/tex]
Thus, the quadratic functions are the ones represented by [tex]\( \text{eq1} \)[/tex] and [tex]\( \text{eq2} \)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.